Bezpośrednie inwestycje zagraniczne napływające a stan środowiska w Chińskiej Republice Ludowej - Kalinowska, Izabela (Gospodarka w Praktyce i Teorii, 2013)
The presented article outlines the inflow of the Foreign Direct Investment and the state of the environment in the People’s Republic of China. The results show the existing coherence between the FDI inflow and the environment.